Response to netakimab in radiographic axial spondyloarthritis patients with different baseline C-reactive protein, sacroiliitis evaluated by MRI and peripheral joint involvement status: a post-hoc analysis of the ASTERA study - Mazurov, Vadim I; Dubinina, Tatiana V; Erdes, Shandor; Lapshina, Svetlana A; Soroka, Nikolay F; Kunder, Elena V; Smirnov, Alexandr V; Eremeeva, Anna V; Zinkina-Orikhan, Arina V; Morozova, Maria A; Gaydukova, Inna Z (Clinical and experimental rheumatology, 2023)
Netakimab is a humanised camelid-derived monoclonal antibody targeting interleukin-17A. Here, we report the results of post-hoc analysis of the ASTERA phase 3 study (NCT03447704, February 27, 2018) in patients with active radiographic axial spondyloarthritis (r-axSpA) grouped by baseline C-reactive protein (CRP), baseline sacroiliac joint (SIJ) inflammation through magnetic resonance imaging (MRI) or presence of peripheral arthritis (PA). In this double-blinded, multicentre, randomised, placebo-controlled, phase 3 ASTERA study, 228 adult patients with active r-axSpA received 120 mg of subcutaneous netakimab or placebo at weeks 0, 1, 2, and thereafter every other week. For the subanalysis, 16-week data of 114 netakimab-treated patients with the available baseline CRP and SIJ MRI were grouped by normal (<5 mg/L) or abnormal (≥5 mg/L) CRP, by the grade of sacroiliitis (SI) based on the SPARCC MRI score <2 (MRI-SI-) or ≥2 (MRI-SI+), or by the presence of PA. ASAS-recommended activity, spinal mobility, and function endpoints for r-axSpA were analysed. At week 16, an improvement in all the outcomes was similar for MRI-SI- and MRI-SI+ patients, except for a change in ASspi-MRI-a which was significantly greater in MRI-SI+. Netakimab was effective regardless of baseline CRP and PA. For patients with CRP ≥5 mg/L, a more pronounced decline in r-axSpA activity was observed with a trend towards the most prominent improvement in ASDAS-CRP and BASDAI for patients with CRP >20 mg/L. Subcutaneous netakimab is effective in patients with r-axSpA irrespective of baseline CRP and inflammation on SIJ MRI. The benefit in patients with high CRP (>20 mg/L) was more pronounced.